A tied Fermi liquid to Luttinger liquid model for nonlinear transport in conducting polymers - Jiawei Wang (Nature Portfolio, 2021)
The mechanism of nonlinear charge transport in doped conducting polymers remains elusive. Here, Wang et al. study charge transport with respect to crystalline degrees of samples and construct a model based on the tied link between Fermi liquids and Luttinger liquids, providing a universal explanation to understand nonlinear charge transport in conducting polymers.